Prenatal ultrasound diagnosis of encephalocele FRONT: A case report - Díaz, Hubertino (2015)
We report a case of frontal encephalocele, unusual presentation of neural duct defects, diagnosed by at 31 weeks of gestation. We describe the ultrasound characteristics of encephalocele (extracranial mass, ventricles dilatation, and cranial defect) and consider some entíties that can simulate ímages of frontal encephalocele for differential diagnosis, such as, optic glioma, hemangioma, teratoma. Other studíes were performed to determine associated malformatiorís, that in this case were negative.